2021
DOI: 10.1111/1365-2435.13963
|View full text |Cite
|
Sign up to set email alerts
|

Cracks in the mirror hypothesis: High specularity does not reduce detection or predation risk

Abstract: 1. Some animals, including certain fish, beetles, spiders and Lepidoptera chrysalises, have such shiny or glossy surfaces that they appear almost mirror-like. A compelling but unsubstantiated hypothesis is that a highly specular or mirror-like appearance enhances survival by reflecting the surrounding environment and reducing detectability.2. We tested this hypothesis by asking human participants to wear a mobile eyetracking device and locate highly realistic mirror-green and diffuse-green replica beetles agai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…Specifically, these studies compared the attack rates (by bird predators) in the wild on replica beetles with either glossy or matte elytra. In one study, survival rates between glossy and matte beetles of a similar green hue placed in natural environments did not differ (Franklin et al, 2022), while a more recent study found that glossy beetles of three different hues were consistently easier to detect for bird predators than matte replicas (Thomas et al, 2014). Thus, while there is not yet much direct evidence to suggest that animals pay attention to glossy objects, it has not been tested in many species or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, these studies compared the attack rates (by bird predators) in the wild on replica beetles with either glossy or matte elytra. In one study, survival rates between glossy and matte beetles of a similar green hue placed in natural environments did not differ (Franklin et al, 2022), while a more recent study found that glossy beetles of three different hues were consistently easier to detect for bird predators than matte replicas (Thomas et al, 2014). Thus, while there is not yet much direct evidence to suggest that animals pay attention to glossy objects, it has not been tested in many species or contexts.…”
Section: Discussionmentioning
confidence: 99%
“…Although the biological significance of these highly metallic appearances is still unclear ( Thomas et al. 2007 ; Franklin et al. 2021 ), it may be premature to exclude a thermal function.…”
Section: Discussionmentioning
confidence: 99%